(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Coronavirus Disease 2019 (COVID-19) affects mainly adult with serious devastating effect in some cases. Most reported COVID-19 in children is asymptomatic or mild. Less is known about severe COVID-19 in children requiring hospitalization, especially from Bangladesh. This study was aimed to describe the clinical presentations, diagnostic findings and outcome of suspected and confirmed pediatric COVID-19 patients admitted at a tertiary care facility in Chattogram district of Bangladesh, by analyzing the hospital records. Materials and methods: This retrospective study was conducted in Chittagong Medical College Hospital. Medi- cal records of consecutive 48 admitted patients in the Isolation Unit of Department of Pediatrics till October 15, 2020 were reviewed. Both suspected and confirmed cases were included. Data regarding age, sex, symptoms, signs, laboratory results, in hospital mortality, duration of hospital stay, need for ICU supports were noted. Results: Of the 48 children, 64.6% were male. Overall median (IQR) age was 2.25 years (11 months-8.97 years) and 58.3% were in the age group of upto 5 years. 12.5% had comorbidity in the form of immuno suppressed state (10.4%), congenital heart disease (6.3%) and chronic kidney diseases (4.2%). Most common clinical features were fever (83.3%) cough (79.2%) breathing difficulty (56.3%) abdominal pain (18.8) vomiting (8.3%) and diarrhoea (6.3%). Chest X-ray findings were patchy opacity (20.8%) unilateral or bilateral consolidation (50.0%). RT-PCR could be done for 33 (68.8%) cases and among them the test was positive in only 5 (15.2%). Overall 7 (14.7%) cases expired and among them 5(71.4%) children of minor age group upto 5 years of age and 2 (2/5, 40%) of them were confirmed cases of COVID-19. Conclusions: In this small series of retrospective study revealed high mortality rate of children hospitalized with COVID-19. So they are at risk for severe COVID-19 which was underestimated in general. JCMCTA 2020 ; 31 (2) : 127-132